2016
DOI: 10.1002/2015jd024187
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nitrate in the snow and atmosphere at Summit, Greenland: Chemistry and transport

Abstract: International audienceAs a major sink of atmospheric nitrogen oxides (NOx = NO + NO2), nitrate (NO3-) in polar snow can reflect the long-range transport of NOx and related species (e.g., PAN). On the other hand, because NO3- in snow can be photolyzed, potentially producing gas-phase NOx locally, NO3- in snow (and thus, ice) may reflect local processes. Here we investigate the relationship between local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 94 publications
7
49
3
Order By: Relevance
“…To further constrain NO 3 − oxidation pathways, we considered δ 18 O‐Δ 17 O relations for major tropospheric O bearing molecules incorporated into NO 3 − (Figure ; Fibiger et al, ; Michalski et al, ). Here we assume that the O isotopic composition of NO 3 − is derived from a mixture between a high δ 18 O‐Δ 17 O end‐member, O 3(terminal) and XO (δ 18 O = 95–115‰; Johnston & Thiemens, ), Δ 17 O =39.3±2.0‰ (Vicars & Savarino, ), and various low δ 18 O‐Δ 17 O end‐members including O 2 /RO 2 /HO 2 (δ 18 O = 23.5‰, Δ 17 O = 0‰; Kroopnick & Craig, ), H 2 O (δ 18 O = −27.5±20‰, Δ 17 O = 0‰) and OH (δ 18 O = ‐70±20‰, Δ 17 O = 0‰) (Michalski et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further constrain NO 3 − oxidation pathways, we considered δ 18 O‐Δ 17 O relations for major tropospheric O bearing molecules incorporated into NO 3 − (Figure ; Fibiger et al, ; Michalski et al, ). Here we assume that the O isotopic composition of NO 3 − is derived from a mixture between a high δ 18 O‐Δ 17 O end‐member, O 3(terminal) and XO (δ 18 O = 95–115‰; Johnston & Thiemens, ), Δ 17 O =39.3±2.0‰ (Vicars & Savarino, ), and various low δ 18 O‐Δ 17 O end‐members including O 2 /RO 2 /HO 2 (δ 18 O = 23.5‰, Δ 17 O = 0‰; Kroopnick & Craig, ), H 2 O (δ 18 O = −27.5±20‰, Δ 17 O = 0‰) and OH (δ 18 O = ‐70±20‰, Δ 17 O = 0‰) (Michalski et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We note that OH may not attain complete isotopic equilibrium with H 2 O vapor in polar regions because of low water mixing ratios (Morin et al, ). If OH maintains some of its O 3 character from O( 1 D), the mixing line between O 3 and OH remains the same, with the O atom incorporated into NO 3 − shifted toward O 3 (Fibiger et al, ). We note that due to the speculative nature of δ 18 O values of some of the major O bearing molecules, it can be difficult to use this to evaluate oxidation pathways quantitatively, but it may provide some additional qualitative constraints.…”
Section: Discussionmentioning
confidence: 99%
“…This factor was also seen to have moderate loadings of MS and Br − , 20-30 %, but with a larger degree of uncertainty. The atmospheric chemistry of NO − 3 is complex, involving a variety of sources, formation mechanisms, and destruction mechanisms; in particular, snow can act as both a sink and a source of atmospheric nitrogen oxides, further complicating the local NO − 3 cycle Ianniello et al, 2002;Morin et al, 2008;Fibiger et al, 2016). Furthermore, the complex processing of NO − 3 was demonstrated in the earlier deposition analysis of these data which suggested that gas-phase deposition was a dominant mechanism of NO − 3 transport to snow (Macdonald et al, 2017).…”
Section: Factor 5: Nitratementioning
confidence: 99%
“…This correlation with H + is in agreement with this factor's low neutralization ratio of 0.04. The low fall/spring levels of this factor may reflect the loss of NO − 3 from snow through photolysis driven by the sunlight availability after polar sunrise (Morin et al, 2008;Fibiger et al, 2016). The highest NO − 3 levels were observed when photolysis was inhibited during the polar sunset from mid-October to late February.…”
Section: Factor 5: Nitratementioning
confidence: 99%
“…This factor was also seen to have moderate loadings of MSA and Br -, 20-30%, but with a larger degree of uncertainty. The atmospheric chemistry of NO3 -is complex, involving a 25 variety of sources, formation mechanisms, and destruction mechanisms; in particular, snow can act as both a sink and a source of atmospheric nitrogen oxides, further complicating the local NO3 -cycle (Morin et al, 2008;Fibiger et al, 2016).…”
Section: Factor 5: Nitratementioning
confidence: 99%